2015
DOI: 10.1017/s1751731115001172
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of visible and near infrared reflectance spectroscopy on fat to authenticate dietary history of lambs

Abstract: Since consumers are showing increased interest in the origin and method of production of their food, it is important to be able to authenticate dietary history of animals by rapid and robust methods used in the ruminant products. Promising breakthroughs have been made in the use of spectroscopic methods on fat to discriminate pasture-fed and concentrate-fed lambs. However, questions remained on their discriminatory ability in more complex feeding conditions, such as concentrate-finishing after pasture-feeding.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Thus, the possibility of combining the visible and near-infrared spectra (350–2500 nm) attracted the attention of the meat industry stakeholders to create a new technology called visible-near infrared spectroscopy (VIS–NIRS). For sheep, the VIS–NIRS has been used for the evaluation of meat attributes in a variety of quantitative applications [ 72 , 73 ]. Table 5 summarizes the research using NIRS and VIS–NIRS to assess meat quality of sheep and goats.…”
Section: Spectroscopic Techniques For Assessment Of Carcass and Mementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the possibility of combining the visible and near-infrared spectra (350–2500 nm) attracted the attention of the meat industry stakeholders to create a new technology called visible-near infrared spectroscopy (VIS–NIRS). For sheep, the VIS–NIRS has been used for the evaluation of meat attributes in a variety of quantitative applications [ 72 , 73 ]. Table 5 summarizes the research using NIRS and VIS–NIRS to assess meat quality of sheep and goats.…”
Section: Spectroscopic Techniques For Assessment Of Carcass and Mementioning
confidence: 99%
“…Besides, VIS–NIRS also estimate taste traits but with modest capacity R 2 < 0.4 [ 78 ]. The VIS–NIRS have also been shown to be of interest for discriminating carcasses of lambs originating in pasture-fed and concentrate-fed diets [ 73 ]. This work shows that it is possible based on perirenal fat to discriminate between 98.5 and 100% of lamb carcasses accurately.…”
Section: Spectroscopic Techniques For Assessment Of Carcass and Mementioning
confidence: 99%
“…There are few studies on the potential of spectroscopic techniques for the determination of the production method (dietary background) of meat. One example is a study conducted by Huang and co-authors [245], who applied reflectance spectroscopy in two spectral ranges (400-700 nm and 400-2500 nm) coupled with PLS-DA to discriminate carcasses of lambs reared with 3 feeding regimes, involving perirenal fat from pasture-fed, concentrate-fed, and concentrate-finished after pasture feeding diets. The results demonstrated that the 3 feeding regimes could be distinguished with overall correct classification rates of 95.1% and 99% for the 400-700 nm and 400-2500 nm spectral ranges, respectively.…”
Section: Meat and Meat Productsmentioning
confidence: 99%
“…Due to the demand of quality and the swelling in price, food adulteration is still quite common in some food products that include milk [1,2], wine [3,4], table oil [5,6], tea [7], coffee [8], and meats [9][10][11]. For example, it has been testified that 20% of the tested livestock meat were assured of counterfeit in Guangdong Province, China, during 2014-2015 [12].…”
Section: Introductionmentioning
confidence: 99%
“…European criminal police organization (EUPOL) and international criminal police organization (INTERPOL) also have collaborated in monitoring food security, resulting in 2500-ton illegal and counterfeit food [13]. Normally, adulteration of meat might occur by substitution of low-priced or even banned meat species for that high-priced one, such as pork adulterated in the beef and mutton or other meat [9][10][11]14]. Counterfeit of common livestock has caused serious social issues, which not only harms the interests of religious-concerned or allergic consumers but also deteriorates the credit of the enterprises [15].…”
Section: Introductionmentioning
confidence: 99%